2016
DOI: 10.1021/acscatal.5b02805
|View full text |Cite
|
Sign up to set email alerts
|

Minimalist Protein Engineering of an Aldolase Provokes Unprecedented Substrate Promiscuity

Abstract: Application of aldolases for the asymmetric synthesis of multifunctional chiral products is hampered by their reputed strict nucleophile (=aldol donor) specificity owing to a mechanistic requirement for creating a carbanion nucleophile in aqueous medium. Here we report that a minimalist engineering can extensively broaden the substrate scope of native D-fructose-6-phosphate aldolase (FSA) from Escherichia coli, for which hydroxyacetone is the most proficient substrate, to accept an unprecedented wide variety o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…Upon increasing steric space in the hydrophobic nucleophile‐binding domain of FSA (i.e., residues L107 and L163), by using simple conservative Leu to Ala replacement, FSA L107A/L163A , the nucleophile repertoire of FSA was largely expanded . Hence, higher ketols; analogues of 1 b ; and bioisosteric ethers, which are analogues of 1 a , with up to seven skeletal atoms, including linear and branched‐chain structures were efficiently converted (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon increasing steric space in the hydrophobic nucleophile‐binding domain of FSA (i.e., residues L107 and L163), by using simple conservative Leu to Ala replacement, FSA L107A/L163A , the nucleophile repertoire of FSA was largely expanded . Hence, higher ketols; analogues of 1 b ; and bioisosteric ethers, which are analogues of 1 a , with up to seven skeletal atoms, including linear and branched‐chain structures were efficiently converted (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…L163A was the critical mutation that created the additional space necessary to accommodate larger substrates in a rather extended conformation, whereas the L107A/L163A variant, which offered the contiguous extra void, now enabled the binding of ketols with chain lengths (at least) of up to C7 carbon atoms …”
Section: Methodsmentioning
confidence: 99%
“…Remarkably, it accepts hydroxyethanal (HE) as an aldehyde rather than a ketone nucleophile (Figure ), which is unparalleled among the aldolases, with the exception of 2‐deoxy‐ d ‐ribose‐5‐phosphate aldolase (DERA), which uses ethanal. More recently, the subtle nucleophile selectivity of wild‐type FSA was dramatically enhanced by minimalist protein engineering . Single or double active site mutations allowed an efficient conversion of larger ketol components with up to seven skeletal atoms.…”
Section: Methodsmentioning
confidence: 99%
“…In a very recent contribution, the same research group demonstrated that the substrate scope of FSA can be spectacularly broadened with a minimum of active site engineering . Optimal results were obtained with the double variant FSA L107A L 163A in which bulky Leu at the active site have been replaced by less hindered Ala.…”
Section: Non‐biomimetic Approaches Using Aldolasesmentioning
confidence: 99%